Peponocephala electra - Russell A. Mittermeier; Don E. Wilson (Lynx Edicions, 2014)
29. Melon-headed Whale Peponocephala electra French: Péponocéphale / German: Breitschnabeldelfin / Spanish: Delfin de cabeza de melon Other common names: Electra Dolphin, Little Killer Whale, Many-toothed Blackfish Taxonomy. Lagenorhynchus electra Gray, 1846, type locality unknown. This species is monotypic. Distribution. Worldwide in tropical and subtropical waters from c.40° N to ¢.35° §, including the Gulf of Mexico, Arabian Sea, Bay of Bengal, South China Sea, and Timor Sea. Descriptive notes. Total length up to 280 cm; weight up to 275 kg. Neonates may be up to 100 cm long and weigh 15-20 kg. Male Melon-headed Whales tend to be slightly larger than females. The Melon-headed Whale is very similar in appearance to the Pygmy Killer Whale (Feresa attenuata). It is moderately robust in stature, with bulbous, although not overly round, head with barely visible beak, tall falcate dorsal fin, and sickle-shaped flippers. More triangularshaped head and more sharply pointed flippers distinguish it from the Pygmy Killer Whale. Skin is dark gray, but darker colored cape may be discernable along back, dipping below dorsal fin. Lips are usually white, and white—to—pale-gray patches are often present on throat and extend along ventral body to urogenital region. Dark band may also extend from blowhole anteriorly along melon, and dark eye patches may extend from eyes up and forward toward front of melon, resulting in a mask-like appearance. Males tend to have longer dorsal fins and flippers, more distinct post-anal humpjust anteriorto tail flukes, and more bulbous melon than females. Young Melonheaded Whales may have more sloping melon than adults. There are 20-25 pairs of small, slender teeth in each jaw. Habitat. Prefer tropical and subtropical waters, and occasional sightings from higher latitudes usually associated with extended warm water currents. The Melon-headed Whale is most abundant in deep, offshore waters and is only found in coastal regions if continental shelf is close to shore, resulting in near-shore deep ...